Differential expression of myc, max and RB1 genes in human gliomas and glioma cell lines. - Hirvonen, H. E. (Nature Publishing Group, 1994)
Deregulated expression of myc proto-oncogenes is implicated in several human neoplasias. We analysed the expression of c-myc, N-myc, L-myc, max and RB1 mRNAs in a panel of human gliomas and glioma cell lines and compared the findings with normal neural cells. The max and RB1 genes were included in the study because their protein products can interact with the Myc proteins, being thus putative modulators of Myc activity. Several gliomas contained c/L-myc mRNAs at levels higher than those in fetal brain, L-myc predominantly in grade II/III and c-myc in grade III gliomas. High-level N-myc expression was detected. In one small-cell glioblastoma and lower levels in five other gliomas. In contrast, glioma cell lines totally lacked N/L-myc expression. The in situ hybridisations revealed mutually exclusive topographic distribution of myc and glial fibrillary acidic protein (GFAP) mRNAs, and a lack of correlation between myc expression and proliferative activity, max and RB1 mRNAs were detected in most tumours and cell lines. The glioma cells displayed interesting alternative splicing patterns of max mRNAs encoding Max proteins which either suppress (Max) or augment (delta Max) the transforming activity of Myc. We conclude that (1) glioma cells in vivo may coexpress several myc genes, thus resembling fetal neural cells; but (2) cultured glioma cells expression only c-myc; (3) myc, max and RB1 are regulated independently in glioma cells; and (4) alternative processing of max mRNA in some glioma cells results in delta Max encoding mRNAs not seen in normal fetal brain. IMAGES: